Single‐Crystal Hybrid Perovskite Platelets on Graphene: A Mixed‐Dimensional Van Der Waals Heterostructure with Strong Interface Coupling. (6th February 2020) - Liu, Zhixiong; You, Lu; Faraji, Nastaran; Lin, Chun‐Ho; Xu, Xiangming; He, Jr‐Hau; Seidel, Jan; Wang, Junling; Alshareef, Husam N.; Wu, Tom
Abstract: Van der Waals (vdW) heterostructures open up excellent prospects in electronic and optoelectronic applications. In this work, mixed‐dimensional metal‐halide perovskite/graphene heterostructures are prepared through selective growth of CH3 NH3 PbBr3 platelets on patterned single‐layer graphene using chemical vapor deposition. Preferred growth of single‐crystal CH3 NH3 PbBr3 platelets on graphene surfaces is achieved, which is accompanied by significant photoluminescence quenching. Raman spectra reveal that perovskite platelets cause p‐type doping in the graphene layer. A significant Fermi level decrease of 272 meV in graphene is estimated, which corresponds to a high doping density of 7.5 × 10 12 cm −2 . Surface potentials measured by Kelvin probe force microscopy indicate a negatively charged perovskite surface under illumination, which is consistent with the upward band bending deduced from conducting atomic force microscopy measurements. Moreover, a field‐effect phototransistor is fabricated using the perovskite/graphene heterostructure channel, and the increased Dirac voltage under illumination confirms an enhanced p‐type character in graphene. These findings enrich the understanding of strong interface coupling in such mixed‐dimensional vdW heterostructures and pave the way toward novel perovskite‐based optoelectronic devices. Abstract : Growth of single‐crystal hybrid perovskite platelets on single‐layer graphene is achieved using a chemical vapor deposition method, forming mixed‐dimensional van der Waals heterostructures. Strong interface interactions are revealed by photoluminescence, Raman, and Kevin probe measurements. The hole transfer from perovskite to graphene under illumination exerts a significant influence on the performance of optoelectronic devices.